Supplementary information for paper "Spatial modelling approach and accounting method affects soil carbon estimates and derived farm-scale carbon payments" - Beka, Stelina (Cranfield University, 2022)
The series of datasets in this document were used to calibrate and validate the three spatial modelling approaches described in the paper.
Keywords: Soil organic carbon.'; 'spatial modelling'; 'calibration sample'; 'validation sample'; 'Carbon Sequestration Science'; 'Environmental Management'